TRAINING ON APPLIED BEHAVIORAL ANALYSIS (ABA) METHODS IN HANDLING CHILDREN WITH SPECIAL NEEDS FOR TEACHERS OF SD CLUSTER III CIAWI BOGOR SUBDISTRICT - Nurmawati, Nurmawati; Ithriyah, Siti (Green Publisher Indonesia, 2022)
This study aims to analyze the applied behavioral analysis training method in dealing with children with special needs. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study concluded that occupational therapy helps children train the muscles of the body and legs to be strong and balanced right and left. Teach which emphasizes children to be able to work purposefully in their community. Sensory integration therapy teaches children how to train the balance of the right brain and left brain to develop in a balanced way. Sone-rise has the main principle of following